Effects of temperature and pH on the total phenolics content and antioxidant activity of Noni (morinda citrifolia Linn.) - Magdadaro, Josephine D.
ABSTRACT Antioxidant rich foods are known to have a key role in decreasing the risks of diseases. The fruits of noni (Morinda citrifolia L.) and various noni products, specially the noni juice, have gained considerable attention over the past few years because of their supposed therapeutic effects on several illnesses. This study entailed the analysis of the antioxidant properties - total phenolics content (TPC) and antioxidant activity (AA) - of noni fruit and the investigation of the effects of temperature (10,30,60,80 and 100°C) and pH (pH 2, 4 and 7) on these properties. Evaluation of the antioxidant properties of three noni products was also done. TPC and AA were analyzed through the Folin-Ciocalteu method and DPPH method, respectively. The TPC of the unprocessed aqueous noni extract was 928.25±0.42 mg/100g gallic acid equivalent (GAE)and 1072.31±0.48 mg/100g tannic acid equivalent (TAE), on dry weight basis. AA was 29.71±2.91% at 6 mg/ml extract concentration. Treatment with various temperature and pH combinations resulted in variable effects on the antioxidant properties of the extracts, depending upon the conditions employed, with the interaction of the two variables being significant (α = 0.05). A quadratic relationship was found between TPC and AA indicating that phenolics may not be the only source of antioxidant activity in noni and that there may be destruction of antioxidants and/or liberation of bound phenolics during the thermal and pH treatments. A survey of the antioxidant properties of three noni products showed a range of 62.33 to 117.10 mg/100g GAE, 70.58 to 134.10 mg/100g TAE and 5.67 to 15.47% AA at 10 mg/ml concentration. Further work needs to be done on the antioxidant properties of noni using other analytical metho